2012
DOI: 10.1128/cvi.00437-12
|View full text |Cite
|
Sign up to set email alerts
|

Immune Complexes Isolated from Patients with Pulmonary Tuberculosis Modulate the Activation and Function of Normal Granulocytes

Abstract: cCirculating immune complexes (ICs) are associated with the pathogenesis of several diseases. Very little is known about the effect of ICs on the host immune response in patients with tuberculosis (TB). The effects of ICs isolated from patients with TB in modulating the release of calcium, cytokines, and granular proteins were studied in normal granulocytes, as were their chemotactic, phagocytic, and oxidative burst processes. ICs from TB patients induced decreased production of cytokines and plateletactivatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…In our present study, we observed almost 5 fold higher ICs in human PKDL subjects. Aberrant glycosylation of proteins in ICs often play important role in pathogenesis of various disease conditions like SLE, Rheumatoid Arthritis and Cancer [ 49 – 52 ]. Recently, CICs has also been identified to play active role in Leishmania infection [ 22 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, we observed almost 5 fold higher ICs in human PKDL subjects. Aberrant glycosylation of proteins in ICs often play important role in pathogenesis of various disease conditions like SLE, Rheumatoid Arthritis and Cancer [ 49 – 52 ]. Recently, CICs has also been identified to play active role in Leishmania infection [ 22 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypergamma-globulinemia was also reported in some systemic diseases like systemic lupus erythematosus (SLE), rheumatoid arthritis, lymphogranuloma venereum, a chronic liver disease like cirrhosis, angioimmunoblastic lymphadenopathy and some classes of lymphomas [ 56 ]. However, infectious diseases like tuberculosis, malaria, filarial, leprosy, influenza are known for comparatively lower expression of CICs [ 24 , 31 , 57 , 58 ]. Asthma was also observed with higher expression of CICs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study monitoring the transition of latent TB to active TB also reported activation of complement pathway genes and increased levels of antigen/antibody complexes in the early stage of Human Immunodeficiency Virus (HIV) associated TB 6 . An earlier study also reported the possible role of CIC's in generating an immune response and regulating variety of immune complexes mediated inflammatory events in tuberculosis 7 . The clinical role of the CIC present in the serum of tuberculosis patients is still unclear, although several studies have tried to demonstrate the specificity of these immune complexes.…”
Section: Introductionmentioning
confidence: 92%
“…for various circulating immune complex associated diseases. Presence of IC's is established in both circulation and in tissues in TB 7 . Thus, in the present study, we made an attempt to explore the proteomic profile of circulating immune complexes from tuberculosis patients in comparison with latent TB and healthy controls.…”
Section: Validation Of Complement C1q Subcomponent Subunit C (C1qc_humentioning
confidence: 99%